The development of GAMA Swab sampling chamber for walk-through sampling in patients with COVID-19 at Gadjah Mada Hospital - Hera Nirwati; Dwi Aris Agung Nugrahaningsih; Siswanto Siswanto; Mahatma Sotya Bawono; Titien Budhiaty; Setyawan Bekti Wibowo; Raden Sumiharto (Journal of Community Empowerment for Health, 2020)
Collecting swab samples from the nasopharynx and oropharynx of patients with COVID-19 is essential in detecting SARS-CoV-2. This procedure potentially produces sufficient droplets. Since SARS-CoV-2 is transmitted through droplets, swab sampling has to be done carefully to prevent the risk of transmission to healthcare workers or the cross-contamination to the environment. The GAMA Swab Sampling Chamber (GSSC) is a positive-pressure chamber designed for collecting swab samples involving the healthcare worker positioned inside, while the patient is outside the chamber. The chamber is designed to minimize the risk of aerosol exposure to the healthcare worker due to leakage or when opening or closing the door. Accordingly, the healthcare worker does not need to use complete personal protective equipment (PPE) as they do when collecting swab samples without the chamber. After several tests to check the safety and the chamber’s function, the GSSC was used at Gadjah Mada Hospital. This chamber had been used to swab 51 asymptomatic patients, 72 suspected patients, and 284 voluntary persons for ten weeks. The results of reverse transcription-polymerase chain reaction (RT-PCR) examination of all samples from asymptomatic patients were negative, while 2 of 72 suspected patients (2.8%) and 4 of 284 voluntary persons (1.4%) had positive RT-PCR results. The use of GSSC can simplify the swab sampling, also reduces the need for PPE usage and a negative pressure isolation room which are limited in the current pandemic situation.